Electroacupuncture Alleviates Cerebral Ischemia/Reperfusion Injury in Rats by Histone H4 Lysine 16 Acetylation-Mediated Autophagy - Xu, Shu-Ying; Lv, He-Qun; Li, Wen-Qian; Hong, Hao; Peng, Yong-Jun; Zhu, Bing-Mei (Frontiers in Psychiatry, 2020)
Abstract: BACKGROUND: Electroacupuncture (EA) has been proven to be effective in treating ischemic stroke; however, the specific mechanism is still elusive. Autophagy is considered as a new target for cerebral ischemia/reperfusion(I/R), while autophagy plays a role of protection or causing rapid cell apoptosis remain unclear. Studies have reported that the reduction in lysine 16 of histone H4 acetylation cohere with autophagy induction. The main purpose of the study was to explore whether EA could alleviate I/R via autophagy mediated histone H4 lysine 16 acetylation in the middle cerebral artery occlusion(MCAO) rat model. METHODS: 120 male Sprague-Dawley rats were divided into five groups: control group, MCAO group, MCAO+EA group, MCAO+EA+hMOF siRNA group, MCAO+EA+Sirt1 inhibitor group. EA was applied to "Baihui" (Du20) and "Renzhong" (DU26) at 5min after modeling and 16h after the first EA intervention. The structure and molecular markers of rat brain were evaluated. RESULTS: EA significantly alleviated I/R injury by upregulating the expression of Sirt1, Beclin1, LC3-II, and downregulating the expression of hMOF and H4K16ac. While Sirt1 inhibitor lowered the increase in Sirt1, Beclin1, LC3-II and enhanced the level of hMOF and H4K16ac expression associated with EA treatment. Besides, ChIP-assay revealed that binding of H4K16ac in Beclin1 promoter region of autophagy target gene was significantly raised in MCAO+EA group and MCAO+EA+hMOF siRNA group. Conclusions: EA treatment inhibited H4K16ac process, facilitated autophagy, and alleviated the I/R injury. These findings suggest that regulating histone H4 lysine 16 acetylation-mediated autophagy may be a key mechanism of EA at Du20 and Du26 to treat I/R.